Al-Muqāranah Bayna ʿIlm al-Lughah al-Taqābulī wa Taḥlīl al-Akhṭāʾ - yoke suryadharma (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2015)
Contrastive Linguistics and Error Analysis are two branches of language teaching studies that belong to the field of Applied Linguistics. Contrastive Linguistics emerged in the 1950s as an approach intended to facilitate the teaching and learning of foreign languages. It gained widespread recognition and application throughout the 1960s and the early 1970s. Subsequently, Error Analysis developed as a complementary approach and, in many respects, as an outgrowth of Contrastive Linguistics. In the field of foreign language education, particularly after the emergence of Error Analysis, scholarly debate arose between proponents of Contrastive Linguistics and advocates of Error Analysis. Rather than examining the causes of this disagreement, the present article focuses on comparing these two approaches in order to achieve a more accurate understanding of their respective theoretical foundations and practical applications. The article aims to provide a comprehensive comparison between Contrastive Linguistics and Error Analysis so that educators and researchers may gain a deeper understanding of both approaches and make effective use of them in foreign language teaching.